AVALIAÇÃO DA APLICAÇÃO DA ENERGIA SOLAR NO AQUECIMENTO DE ÁGUA - Alves, João Carlos Curty (2010)
This dissertation analyzes the systems for heating of water by solar energy and develops the concepts of Energy Efficiency, with the objective of improvement implementation of the resources destined by the Federal Government for this purpose. It s highlight objective is to analyze the economical viability of the substitution of the conventional systems of heating of water by solar systems in the consumers of the residential class, specifically in those of the higher social classes, without passing out on the analysis of the viability and suggestion of solutions for the less favored classes. Before the fact that the practices and investments in Energy Efficiency are contained in an including politics of observance to the beginnings of preservation of the Ecosystem, also harnessed with the subject of the Brazilian electric system and with the Energy Head office, the study also contemplates the approach of these two subjects, for the fact that in first analysis, the devices for heating of water for solar energy need to be understood as a virtual source for generation of energy. It was verified the state of the art of this technology and the evolution of the capacity installed at other countries of the world as well as, the needing of give an obligatory direction to the existents resources who are destined to the Energy Efficiency for Projects of heating of water by solar energy and also there must be better involvement of government both in terms of investment and the need for better targeting and better awareness of the population with respect to the real benefits of water heating by solar energy.